Midazolam plasma concentration after anesthesia premedication in clinical routine - an observational study. Issue 1 (December 2016) - Steiner, C.; Steurer, M.; Mueller, D.; Zueger, M.; Dullenkopf, A.
Abstract Background Midazolam is commonly used as a pre-anesthesia anxiolytic. It`s elimination may not be fast enough for short procedures. In orally premedicated patients we obtained midazolam plasma concentrations at the end of surgical procedures and compared those to concentrations at anesthesia induction. Methods The study was conducted prospectively with consent of the local ethics committee (Ethikkomission Kanton Thurgau, Switzerland) and carried out with written informed consent of each patient. Female patients aged 20 to 60 years undergoing elective procedures with general anesthesia were included, and were divided in two groups according to the planned surgical time: group S (<30 min) and group L (90–120 min), respectively. All patients received 7.5 mg Midazolam po as premedication. Blood samples were drawn at anesthesia induction, and at the end of surgery. Data were compared with t-test (independent samples; significance levelp <0.05). Results Twenty-five patients per group were included. Four patients were excluded from analysis, since midazolam was not detectable in any samples. Time of premedication to the 1st blood sample was not statistically different between groups, neither were Midazolam plasma levels at this time point (p  = 0.94). None of the patients from group L (n  = 24), but five patients in group S (n  = 22) did have a higher plasma level of Midazolam at the end of the case compared to the beginning. Conclusions The elimination half-life of oral Midazolam can lead to higher plasma levels at the end of a short procedure compared to those at induction of anesthesia. Trial registration German Clinical Trials Register (Deutsches Register Klinischer Studien), DRKS00005429 ; date of registration 3rd January 2014